Comparative Study of Tsukamoto and Sugeno's Method in Determining Total Demand Based on Sales and Inventory (Case Study of Duta Ponsel Sukamerindu) - Rio Sefrin Alfa Meta; Yupianti Yupianti; Rina Julita (Penerbit Jurnal Indonesia, 2021)
Duta Ponsel is one of the largest stores in Bengkulu City that sells various kinds of smartphones and accessories according to the type of smartphone. Duta Ponsel has implemented information technology in its store business therefore it can facilitate data processing and sales of goods. However, the application is only limited to data management. In fact, these data can help support the sales strategy at Duta Ponsel. This comparison application of the Tsukamoto Method and the Sugeno Method can predict the number of requests for smartphone accessories by entering the amount of inventory and the number of sales. In this application, the processing time that occurs in Fuzzy Tsukamoto and Fuzzy Sugeno has been integrated, making it easier to see the comparison between the two methods. Comparative study of Tsukamoto Method and Sugeno Method in Determining Total Demand Based on Sales and Inventory at Duta Ponsel Sukamerindu seen from 2 (two) aspects of comparison, namely the final result of demand prediction and processing time. To assist the comparison process, an application was built using the Visual Basic .Net programming language with SQL Server 2008r2 database. Based on the results of the tests that have been carried out, the application is able to display comparative information between the Tsukamoto Method and the Sugeno Method through 2 (two) aspects, namely the final result of demand prediction and processing time. Based on the processing time, the Sugeno Method is faster than the Tsukamoto Method